Religiusitas Islam dalam Serat Wedhatama Pupuh Gambuh - Rudi Permono Putro; Muhammad Rohmadi; Ani Rakhmawati; Kundharu Saddhono (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2021)
Religion and culture are often confronted diametrically, including Islam and Javanese culture. However, the intellectual, cultural treasures of Javanese cultural heritage in Serat Wedhatama show that this serat has a dimension of Islamic religiosity. The content of the Serat Wedhatama is essential for strengthening the practice of Islamic religiosity in society amid the moral degradation of the nation's generation. This research has a necessary contribution to inculcating religious and cultural values in the nation's generation. The research used a qualitative approach to reveal the dimensions of Islamic religiosity in Serat Wedhatama Pupuh Gambuh by KGPAA Mangkunegara IV. The study of the manuscript's contents shows that Serat Wedhatama Pupuh Gambuh contains five dimensions of Islamic religiosity: the dimension of belief, dimensions of religious practice, the dimension of treachery, and religious knowledge; and practice dimensions. This study also confirms a relationship between (Serat Jawa) as a product of culture and religious values. The values in Pupuh Gambuh Wedhatama Fiber can be used as parameters and guidelines for life. This study can also be used to answer the conditions of the people who are amid deculturation and de-religiosity.